(untitled) (The Geographic Base, 2019)
Kanchanpur district is one of the disaster-prone districts identified by Nepal Risk Reduction Consortium (NRRC). Every year the community of Kanchanpur district are affected by multi-disaster primarily flood. The most communities are highly vulnerable due to the poverty, disadvantage caste and ethnicity, hazard, education etc. This study endeavour to explore the status of community initiative to build up disaster resilient. This study covers 10 villages of Mahakali river basin in Kanchanpur district. The villages are under the process of disaster resilience through establishing Community Disaster Management Committee (CDMC), who supports to get access to disaster risk reduction (DRR) information, vulnerability and capacity assessment and developing trained man power for preparedness and response.